Prickly pear polygalacturonase gene: cDNA cloning and transcript accumulation during ethylene treatment, cold storage and wounding - Rosas-Cárdenas, F.F.; Valderrama-Chairez, M.L.; Cruz-Hernandez, A.; Paredes-Lopez, O.
Polygalacturonase (PG; EC 3.2.1.6.9)has been the most widely studied cell wall hydrolase in fruit ripening. Degenerate oligonucleotides corresponding to conserved regions from reported sequences were used as primers for RT-PCR to amplify mRNA extracted from middle ripe fruit. Cloning and characterization of a cDNA OsPG showed a 282 bp product with a predicted sequence of 94 amino acids. The peptide exhibited a high identity with previously reported fruit PGs. Northern blot analysis of the messenger showed a 1.7 kb transcript induced during prickly pear ripening. It was found by Southern blot analysis that there is one copy of this gene. The OsPG mRNA expression is sensitive to ethylene, cold storage and wounding.
Keywords: CELL WALL; FRUIT RIPENING; POLYGALACTURONASE; PRICKLY PEAR; SOFTENING; NON-CLIMACTERIC